On pseudobounded and premeage paratopological groups - A.V. Ravsky; T.O. Banakh (Математичні Студії)
Let $G$ be a paratopological group. Following F.~Lin and S.~Lin, we say that the group $G$ is pseudobounded, if for any neighborhood $U$ of the identity of $G$, there exists a natural number $n$ such that $U^n=G$. The group $G$ is $ω$-pseudobounded, if for any neighborhood $U$ of the identity of $G$, the group $G$ is a union of sets $U^n$, where $n$ is a natural number. The group $G$ is premeager, if $G\ne N^n$ for any nowhere dense subset $N$ of $G$ and any positive integer $n$. In this paper we investigate relations between the above classes of groups and answer some questions posed by F. Lin, S. Lin, and S\'anchez.